ECONOMIC EVALUATION OF PHARMACOGENETIC-GUIDED PRESCRIBING IN PRECISION MEDICINE FOR CARDIOVASCULAR DISEASES: AN EVIDENCE SYNTHESIS FROM ASIAN COUNTRIES - Halilintar, Via Dolorosa; Lonah, Lonah; Pujiyanto, Pujiyanto (Jurnal Manajemen Kesehatan Indonesia, 2024)
Precision medicine, particularly pharmacogenetic-guided approaches, has emerged as a promising tool to optimize treatment strategies for cardiovascular disease. However, the economic evaluation of these approaches in Asian populations remains underexplored. This review study aimed to synthesize evidence on the implementation, methodology, research gaps, and limitations of pharmacogenetic-guided precision medicine in cardiovascular disease among the Asian population. A comprehensive search of electronic databases (Pubmed, Embase, Google Scholar and Cochrane Library) was conducted to identify relevant studies. The data were extracted and synthesized to address the study objectives A total of 12 studies were included in the analysis. Economic evaluation studies of pharmacogenetic-guided precision medicine in cardiovascular disease management in Asian countries are still limited, with precision medicine interventions often requiring high resources. The sampling process remains a challenge in conducting economic evaluation studies, and there are limitations in obtaining clinical outcome descriptions from real-world evidence, as most studies rely on literature reviews or modeling-based approaches. Furthermore, most studies use a provider or healthcare cost perspective, limiting the comprehensiveness of cost information. This evidence synthesis highlights the potential for pharmacogenetic-guided precision medicine in cardiovascular disease management among the Asian population, as well as the current challenges and limitations in conducting economic evaluations. Further research is needed to address these issues, develop more robust sampling strategies, obtain real-world clinical outcome data, and provide comprehensive cost information to inform clinical practice and healthcare policy in the region.